2015
DOI: 10.1093/pcp/pcv101
|View full text |Cite
|
Sign up to set email alerts
|

Heteromannan and Heteroxylan Cell Wall Polysaccharides Display Different Dynamics During the Elongation and Secondary Cell Wall Deposition Phases of Cotton Fiber Cell Development

Abstract: The roles of non-cellulosic polysaccharides in cotton fiber development are poorly understood. Combining glycan microarrays and in situ analyses with monoclonal antibodies, polysaccharide linkage analyses and transcript profiling, the occurrence of heteromannan and heteroxylan polysaccharides and related genes in developing and mature cotton (Gossypium spp.) fibers has been determined. Comparative analyses on cotton fibers at selected days post-anthesis indicate different temporal and spatial regulation of het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 57 publications
2
24
0
Order By: Relevance
“…Also, higher expressions of sucrose synthase, beta‐galactosidase ( BGAL ), beta‐D‐xylosidase ( BXL ), xyloglucan endotransglucosylase ( XET ), glucan endo‐1,3‐beta‐glucosidase ( BGL ) and phosphoenolpyruvate carboxykinase ( PEPC ) in fibers of the GhFSN1 OE transgenic cotton may be closely involved in the massive synthesis of cellulose. Previous studies also revealed that lignin and xylan are important components during the SCW deposition phase of cotton fiber development (Han et al ., ; Hernandez‐Gomez et al ., ). In this study, our transcriptome data revealed that xylan and lignin biosynthetic genes (such as homologs of AtIRX9/9‐L , AtIRX10/10‐L , AtIRX14/14‐L , AtGUX1‐3 and AtDUF579s and AtDUF231s ) were up‐regulated in the GhFSN1 OE transgenic fibers (Table S4).…”
Section: Discussionmentioning
confidence: 97%
“…Also, higher expressions of sucrose synthase, beta‐galactosidase ( BGAL ), beta‐D‐xylosidase ( BXL ), xyloglucan endotransglucosylase ( XET ), glucan endo‐1,3‐beta‐glucosidase ( BGL ) and phosphoenolpyruvate carboxykinase ( PEPC ) in fibers of the GhFSN1 OE transgenic cotton may be closely involved in the massive synthesis of cellulose. Previous studies also revealed that lignin and xylan are important components during the SCW deposition phase of cotton fiber development (Han et al ., ; Hernandez‐Gomez et al ., ). In this study, our transcriptome data revealed that xylan and lignin biosynthetic genes (such as homologs of AtIRX9/9‐L , AtIRX10/10‐L , AtIRX14/14‐L , AtGUX1‐3 and AtDUF579s and AtDUF231s ) were up‐regulated in the GhFSN1 OE transgenic fibers (Table S4).…”
Section: Discussionmentioning
confidence: 97%
“…Even though the fibres are made up largely of cellulose, other less abundant polysaccharides are important in ways that may be specific to cotton fibre cells. For example, developing cotton fibres transiently synthesise callose at the onset of secondary wall deposition (Maltby et al 1979) and Hernandez-Gomez et al (2015a) found xylan and cellulose transcript abundance to be tightly correlated during fiber development.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the Gossypium genus, the species G. hirsutum, G. barbadense, G. arboreum and G. herbaceum have been domesticated for fibre production (Hernandez-Gomez et al, 2015). While G. hirsutum accounts for the majority of the cotton fibre production due to its high yield and wide environmental adaptability, G. barbadense presents superior fibre quality (i.e.…”
Section: Introductionmentioning
confidence: 99%